Tightening Up the EU's Policy Towards Large Platforms in the Fight against Disinformation - Espaliú Berdud, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In recent years we have witnessed a tightening of EU policy in the fight against disinformation in relation to online platforms. There has been a shift from soft law policies where platforms did not assume strong obligations, to coregulatory measures where platforms, particularly large ones, assume stronger obligations. This is due to the limited effectiveness of initial policies in this area and the realisation of the seriousness of the disinformation challenge, such as the Covid pandemic and the use of disinformation by Russia against the interests of the EU and its member states.